Perencanaan Tebal Perkerasan Lentur Menggunakan Metode Bina Marga (MDPJ 2017) Pada Ruas Jalan Cisomang – Rajamandala - Busnial Busnial (Pusat Riset dan Inovasi Nasional, 2022)
In general, making a plan must be based on data, where the data is obtained from survey results and test results. The Cisomang - Rajamandala road section is a section that is frequently traversed by overloaded vehicles so that it can damage the road pavement structure and the pavement structure used is flexible pavement. In a flexible pavement thickness planning, there are generally several methods used to calculate the thickness of a pavement. There is one method from Bina Marga, namely the 2017 Road Pavement Design Manual (MDPJ). Using this method will produce simple calculations with specific results such as in terms of surface layer thickness to the foundation layer in a road construction plan. This study aims to make planning for thick flexible pavement using the Bina Marga method (MDPJ 2017) on the Cisomang - Rajamandala road section with research points along 1 KM and the total length of the section is 43.43 KM. This research is a quantitative research using survey data and testing data. This study aims to make flexible pavement thickness planning using the Bina Marga method (MDPJ 2017) on the Cisomang - Rajamandala road section with research points along 1 KM and the overall length of the section is 43.43 km. This research is a quantitative research with survey data (LHRT) and test data. The results of calculations based on data and analysis carried out in this study indicate that planning the thickness of flexible pavement for the Cisomang - Rajamandala road section using the Bina Marga method (MDPJ 2017) along 1 KM, namely using a pavement structure of type FFF6 with the following details: Surface Layer (AC WC ): 4 CM, Layer (AC BC) : 6 CM, Layer (AC Base): 16 CM, Layer Foundation: 300 CM.